Predictive imaging of chemotherapeutic response in a transgenic mouse model of pancreatic cancer. Issue 3 (15th April 2016) - Wang, Ping; Yoo, Byunghee; Sherman, Sarah; Mukherjee, Pinku; Ross, Alana; Pantazopoulos, Pamela; Petkova, Victoria; Farrar, Christian; Medarova, Zdravka; Moore, Anna
Abstract : The underglycosylated mucin 1 tumor antigen (uMUC1) is a biomarker that forecasts the progression of adenocarcinomas. In this study, we evaluated the utility of a dual‐modality molecular imaging approach based on targeting uMUC1 for monitoring chemotherapeutic response in a transgenic murine model of pancreatic cancer (KCM triple transgenic mice). An uMUC1‐specific contrast agent (MN‐EPPT) was synthesized for use with magnetic resonance imaging (MRI) and fluorescence optical imaging. It consisted of dextran‐coated iron oxide nanoparticles conjugated to the near infrared fluorescent dye Cy5.5 and to a uMUC1‐specific peptide (EPPT). KCM triple transgenic mice were given gemcitabine as chemotherapy while control animals received saline injections following the same schedule. Changes in uMUC1 levels following chemotherapy were monitored using T2‐weighted MRI and optical imaging before and 24 hr after injection of the MN‐EPPT. uMUC1 expression in tumors from both groups was evaluated by histology and qRT‐PCR. We observed that the average delta‐T2 in the gemcitabine‐treated group was significantly reduced compared to the control group indicating lower accumulation of MN‐EPPT, and correspondingly, a lower level of uMUC1 expression. In vivo optical imaging confirmed the MRI findings. Fluorescence microscopy of pancreatic tumor sections showed a lower level of uMUC1 expression in the gemcitabine‐treated group compared to the control, which was confirmed by qRT‐PCR. Our data proved that changes in uMUC1 expression after gemcitabine chemotherapy could be evaluated using MN‐EPPT‐enhanced in vivo MR and optical imaging. These results suggest that the uMUC1‐targeted imaging approach could provide a useful tool for the predictive assessment of therapeutic response. Abstract : What's new? During treatment, cancer cells often undergo molecular changes long before tumor morphology changes. Biomarkers to detect these changes could enhance therapy by allowing earlier analysis. In this study in mice, the authors developed a non‐invasive technique for imaging cellular levels of the tumor antigen uMUC1, which is overexpressed in more than 50% of all cancers. They found that uMUC1 expression drops when pancreatic cancer begins to respond to therapy. This imaging technique may allow the early assessment of tumor response and prognosis.